Lithium ion secondary battery

By using a combination of graphite material with a high silicon doping amount and a silicon-carbon material in the negative electrode sheet of the lithium-ion battery, and adding lithium supplement agent to the positive electrode sheet, the problem of difficult to take into account both the cycle stability and the low cycle expansion rate when improving the energy density of the lithium-ion battery is solved, and the effects of high energy density, long cycle life and low cycle expansion rate are achieved.

CN119890405AActive Publication Date: 2025-04-25ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411995741.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

While increasing the energy density, existing lithium-ion batteries are difficult to take into account excellent cycle stability and low cycle expansion rates, especially due to the high-temperature gas production and active lithium consumption caused by the excessive use of fluorovinyl carbonate in the electrolyte.

Method used

By using a combination of high silicon doped graphite material and silicon carbon material in the negative electrode sheet, combining the particle size and structural design of specific graphite materials and silicon carbon materials, the content of fluorovinyl carbonate in the electrolyte is regulated, and lithium supplementation agent is added to the positive electrode sheet to reserve active lithium to reduce the amount of FEC in the electrolyte.

Benefits of technology

The high energy density, long cycle life and low cycle expansion rate of lithium-ion secondary batteries are achieved, avoiding the adverse effects of high temperature performance and excessive consumption of active lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890405A_ABST
    Figure CN119890405A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion secondary battery. Comprising a negative plate and electrolyte, the negative plate comprises a negative current collector and a negative active coating positioned on at least one side surface of the negative current collector, and the negative active coating comprises a negative active substance; the negative active material comprises a graphite material and a silicon carbon material; the graphite material comprises secondary particles, and the silicon carbon material comprises primary spherical particles and secondary spherical particles formed by a plurality of primary spherical particles; the electrolyte comprises fluoroethylene carbonate, the mass content c2 of the fluoroethylene carbonate in the electrolyte is less than or equal to 30, and the unit is%; the mass content of the element Si in the negative electrode active coating is 1.5%-15%; the average particle size d2 of the secondary particles is 6 [mu] m-20 [mu] m; the average particle size d1 of the primary spherical particles is 1 [mu] m-6 [mu] m. The lithium ion secondary battery according to the present invention can give consideration to both high energy density and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] Lithium-ion batteries have great potential in electronic devices, electric vehicles, etc. Current technology is committed to improving the energy density of batteries. Silicon-based materials are considered to be key materials for improving battery energy density because they have a higher theoretical specific capacity (about 3600mAh / g), which is much higher than the theoretical specific capacity of graphite materials (about 370mAh / g). The current method for improving battery energy density is mainly to increase the content of silicon-based materials in the negative electrode sheet, but silicon-based materials have a volume expansion problem. Usually, in order to improve the volume expansion of silicon-based materials, fluoroethylene carbonate is added to the electrolyte. Fluorinated ethylene carbonate can form a film at the negative electrode, thereby inhibiting the volume expansion of silicon-based materials. However, excessive content of fluoroethylene carbonate will lead to high-temperature gas production, which is not conducive to the cycle performance of the battery. And as the content of silicon-based materials increases, the side reactions between the negative electrode sheet and the electrolyte intensify, and the active lithium will be seriously consumed, which is also not conducive to the cycle performance of the battery.

[0003] Therefore, it is very important to improve both the energy density and cycle performance of the battery. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that energy density and cycle performance cannot be taken into account in the prior art, and provide a lithium ion secondary battery (hereinafter referred to as a battery). The negative electrode sheet of the present invention has a high silicon content and a suitable fluoroethylene carbonate content, and a specific graphite material and a silicon-carbon material are used in combination, so that the lithium ion secondary battery (hereinafter referred to as a battery) including the negative electrode sheet has both high energy density and excellent cycle stability.

[0005] After extensive research, the inventors of the present invention have found that by improving the graphite material and silicon-carbon material in the negative electrode, the amount of silicon doped in the negative electrode sheet can be significantly increased while ensuring that the battery has good cycle stability, and the compaction density of the negative electrode sheet can be increased, so that the battery has a high energy density. In addition, by controlling the content of fluoroethylene carbonate in the electrolyte, the fluoroethylene carbonate will not have an adverse effect on the high temperature performance of the battery, further improving the cycle performance of the battery.

[0006] By regulating the average particle size of the primary spherical particles in the silicon-carbon material, the battery can have both high energy density and good cycle stability. This is because: the conventionally used silicon-carbon material is blocky, and the average particle size is about 6μm-12μm, and the hardness of the silicon-carbon material is relatively large. Therefore, the conventionally used silicon-carbon particles have poor conductivity and it is difficult to achieve a large compaction density, which leads to the conventionally used silicon-carbon materials in high silicon-doped systems, especially 5% or more silicon-doped systems (that is, the silicon content in the negative electrode active coating reaches more than 5%). It is difficult to ensure the excellent cycle performance of the battery. In the present invention, a silicon-carbon material including primary spherical particles and secondary spherical particles formed by the primary spherical particles is used. Primary spherical particles with smaller particle sizes are beneficial to improving the energy density of the battery; however, due to their small particle size, the specific surface area is larger, resulting in a corresponding increase in the risk of side reactions with the electrolyte, and poor stability. The secondary spherical particles with larger particle sizes have a smaller surface area, so the risk of side reactions with the electrolyte is lower and the stability is better; however, due to their large particle size, it is difficult to achieve a large compaction density, so it will affect the energy density of the battery. The combination of primary spherical particles and secondary spherical particles is not only conducive to improving the conductivity of the silicon-carbon material itself, but also can improve the compaction of the negative electrode sheet, so that the silicon content in the negative electrode active coating reaches more than 5%, thereby increasing the energy density of the battery. In addition, it can also reduce the risk of side reactions between the silicon-carbon material and the electrolyte, which is conducive to improving the cycle stability of the battery.

[0007] On the basis of the above silicon-carbon materials, the inventors of the present invention use a specific graphite material in combination. By adjusting the structure and particle size of the graphite material, the graphite material includes secondary particles formed by a number of primary particles, and the average particle size of the secondary particles is 6μm-20μm, which can further improve the energy density of the battery. Compared with the graphite material of the primary particles, the secondary particles of the graphite material of a specific particle size have better pressure resistance and can improve the energy density of the battery. Therefore, the graphite material has a high degree of matching with the specific silicon-carbon material, which is conducive to the improvement of the energy density of the battery.

[0008] Based on this, the inventor of the present invention proposed the following solution:

[0009] A lithium-ion secondary battery comprises a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector, wherein the negative electrode active coating comprises a negative electrode active substance; the negative electrode active substance comprises a graphite material and a silicon-carbon material; the graphite material comprises secondary particles, and the silicon-carbon material comprises primary spherical particles and secondary spherical particles formed by a plurality of the primary spherical particles; the mass content of element Si in the negative electrode active coating is 1.5%-15%; the average particle size d2 of the secondary particles is 6μm-20μm; the average particle size d1 of the primary spherical particles is 1μm-6μm; the electrolyte comprises fluoroethylene carbonate, and the mass content of fluoroethylene carbonate in the electrolyte is c2≤30, in %.

[0010] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: the battery of the present invention has high energy density, long cycle life and low cycle expansion rate.

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Shown is a scanning electron microscope (SEM) image of a cross section of a negative electrode sheet along the thickness direction in an example of the present invention.

[0013] Figure 2 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 2 (a) The grooves are arranged continuously; Figure 2 (b) The grooves are arranged in sections.

[0014] Figure 3 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 3 (a)- Figure 3 The two long sides of the groove in (c) are straight lines. Figure 3 The two long sides of the groove in (d) are curved.

[0015] Figure 4 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 4 (a) is the case where two adjacent long sides are straight and parallel. Figure 4 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 4(c) is the case where two adjacent long sides are curved lines.

[0016] Figure 5 FIG. 1 is a schematic diagram showing the structure of a winding core in an example of the present invention.

[0017] Figure 6 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 6 (a) is a top view, Figure 6 (b) is a cross-sectional view along the thickness direction.

[0018] Figure 7 FIG. 1 is a schematic top view of the first surface of the positive electrode sheet in an example of the present invention. DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0020] The present invention provides a lithium-ion secondary battery, which includes a negative electrode sheet and an electrolyte. The negative electrode sheet may include a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector. The negative electrode active coating may include a negative electrode active material, and the negative electrode active material may include a graphite material and a silicon-carbon material. The graphite material includes, for example, artificial graphite and / or natural graphite. The silicon-carbon material refers to a composite material including elemental carbon and elemental silicon, for example, a material formed by filling (including partially filling or completely filling) the pores of porous carbon with silicon and / or oxidized silicon.

[0021] In the present invention, the graphite material may include secondary particles. The secondary particles are formed by a plurality of primary particles, and the “several” means that the number of the primary particles forming the secondary particles is greater than or equal to 2. The silicon-carbon material may include primary spherical particles and secondary spherical particles formed by a plurality of the primary spherical particles. The “several” means that the number of the primary spherical particles forming the secondary spherical particles is greater than or equal to 2. Figure 1 The figure shows a scanning electron microscope (SEM) image of a cross section of a negative electrode sheet in an example of the present invention along the thickness direction. It can be seen from the figure that the silicon-carbon material includes primary spherical particles and secondary spherical particles formed by a plurality of primary spherical particles. Among them, the black circle frame in the figure is the primary spherical particle, and the black square frame is the secondary spherical particle.

[0022] In the present invention, the mass content of element Si in the negative electrode active coating can be 1.5%-15%, for example, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.

[0023] In one example, the mass content of element Si in the negative electrode active coating is 3.5%-12%.

[0024] In the present invention, the mass content of element Si in the negative electrode active coating can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in dimethyl carbonate (DMC) solvent for 12 hours, it is then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and after drying, the negative electrode sheet is treated at a high temperature of 400°C in an inert atmosphere for 2 hours (for example, in a tubular furnace, under a nitrogen or argon atmosphere), and the negative electrode active coating can be peeled off from the negative electrode current collector, and the negative electrode active coating is collected as a test sample. Using a thermogravimetric analyzer (for example, a TGA 550 thermogravimetric analyzer), the test sample amount is 5mg-15mg, and the temperature is increased from room temperature (25°C) to 900°C at a heating rate of 10°C / min in an air or oxygen atmosphere, and kept at 900°C for 40min, so that the non-silicon components in the negative electrode active coating are volatilized while the silicon can be fully oxidized to silicon dioxide. The remaining substance is the ash of the negative electrode active coating. The mass content of element Si in the negative electrode active coating can be calculated based on the mass of the ash. The calculation formula is as follows: mass content of element Si in the negative electrode active coating = 7×mass of ash / (15×mass of test sample).

[0025] In the present invention, the average particle size d2 of the secondary particles can be 6μm-20μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.

[0026] In one example, d2 is 10 μm-15 μm.

[0027] In the present invention, the average particle size d2 of the secondary particles can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasonication, and dried, and the obtained sample is dispersed in deionized water containing nonylphenol polyoxyethylene ether (wherein the mass content of nonylphenol polyoxyethylene ether is 0.02%-0.03%) to form a mixture, ultrasonicated for 2 minutes, and then tested using a Malvern particle size tester, and the median particle size Dv50 data obtained is the average particle size d2 of the secondary particles. Due to the specific composition and particle size of the graphite material and the silicon-carbon material in the present invention, the silicon-carbon material has little effect on the average particle size of the secondary particles of the graphite material, and therefore, the data obtained by the above test method is the average particle size of the secondary particles.

[0028] In the present invention, the average particle size d1 of the primary spherical particles may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm.

[0029] In one example, d1 is 3 μm-5 μm.

[0030] In the present invention, the average particle size d1 of the primary spherical particles can be obtained by testing conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode sheet is cut by an argon ion milling instrument CP laser, and then observed by SEM (using the high voltage mode (Back-scattered Electrons BSE)). In this mode, the contrast of the silicon-carbon material is brighter (which can be used to distinguish the graphite material and the conductive agent in the negative electrode active coating), and at least 20 primary spherical particles are randomly selected at a 5K magnification, and the particle size of each primary spherical particle is measured to take the average value. If the number of primary spherical particles is less than 20 at a 5K magnification, then a mirror image is taken until 20 primary spherical particles are measured.

[0031] In the present invention, the electrolyte may include fluoroethylene carbonate (FEC). The mass content of FEC in the electrolyte is c2≤30, in %, such as 30%, 25%, 20%, 15%, 10%, 9% or 8%.

[0032] In one example, c2 is 8%-30%.

[0033] In the present invention, the mass content c2 of FEC in the electrolyte can be measured by conventional methods in the art, such as gas chromatography-mass spectrometry (GC-MS).

[0034] In the present invention, the mass content of element Si in the silicon-carbon material can be 30%-80%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0035] In the present invention, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.1-0.9 of the total amount of the primary spherical particles and the secondary spherical particles, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.

[0036] In one example, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.3-0.8 of the total amount of the primary spherical particles and the secondary spherical particles.

[0037] In the present invention, the number of the primary spherical particles and the number of the secondary spherical particles can be tested and obtained by conventional methods in the art. For example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet. The negative electrode sheet is cut along the thickness direction of the negative electrode sheet using an argon ion milling instrument CP laser, and then observed using SEM (using high voltage mode) to obtain a mirror image of the cross section of the negative electrode sheet along the thickness direction. It is observed at a magnification of 1K, and at least 20 mirror images of different cross sections are selected. The number of primary spherical particles and the number of secondary spherical particles in each mirror image are counted respectively, and the average value is taken.

[0038] By adjusting the ratio of primary spherical particles to secondary spherical particles in the negative electrode active coating, the silicon-carbon material can be arranged more closely, which is not only conducive to further improving the conductivity of the silicon-carbon material itself, but also to further improve the compaction of the negative electrode sheet, thereby increasing the energy density of the battery. And when the primary spherical particles and secondary spherical particles are mixed in a specific ratio, the risk of side reactions between the silicon-carbon material and the electrolyte can be further reduced, which is conducive to improving the cycle stability of the battery.

[0039] In the present invention, 1.33≤d2 / d1≤20, for example, 1.33, 1.5, 1.67, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.

[0040] In one example, 1.5≤d2 / d1≤15.

[0041] In one example, 2≤d2 / d1≤5.

[0042] For high silicon-doped battery systems, the advantages of high silicon-doping can be maximized by ensuring high compaction and low expansion of the negative electrode sheet. Therefore, the silicon-carbon material is mixed with a graphite material having secondary particles. When the ratio of the average particle size of the secondary particles to the average particle size of the primary spherical particles is within a specific range, the graphite material and the silicon-carbon material are matched to make the orientation consistency of the negative electrode active material better, which is beneficial to reduce the cycle expansion rate of the negative electrode sheet. When d2 / d1 is too large (for example, greater than 20), the particle size of the secondary graphite particles is too large relative to the particle size of the primary silicon-carbon spherical particles, and the conductivity of the graphite material with a larger particle size is poor, resulting in poor dynamic performance of the negative electrode sheet, which is not conducive to the cycle life of the battery; or the silicon-carbon material with a smaller particle size is prone to agglomeration and poor dispersibility. When d2 / d1 is too small (for example, less than 1.33), the particle size of the secondary graphite particles is too small relative to the particle size of the primary silicon-carbon spherical particles. The graphite material with a smaller particle size is not pressure-resistant, which affects the improvement of the compaction density of the negative electrode sheet and thus affects the energy density of the battery; or the silicon-carbon material with a larger particle size has poor conductivity, which affects the dynamic properties of the negative electrode sheet, and the particles are not pressure-resistant and easily broken.

[0043] In the present invention, the OI value V of the negative electrode active coating is OI , the sphericity s of the primary spherical particles and the average particle size d1 (in μm) of the primary spherical particles satisfy: 10≤V OI / s≤35 (e.g., 10, 15, 20, 25, 30 or 35), and 2≤V OI / d1≤15 (for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15).

[0044] In one example, 12 ≤ V OI / s≤22, and 2.5≤V OI / d1≤5.5.

[0045] In one example, 15 ≤ V OI / s≤20, and 3.5≤V OI / d1≤4.

[0046] The OI value of the negative electrode active coating, the sphericity of the primary spherical particles and the average particle size of the primary spherical particles can all affect the expansion rate of the negative electrode sheet in the thickness direction to a certain extent. Specifically: The OI value of the negative electrode active coating represents the overall orientation of the negative electrode active material. The smaller the OI value, the smaller the expansion rate of the negative electrode active material in the thickness direction of the battery. The higher the sphericity of the primary spherical particles, the more equal the probability of expansion in all directions, that is, the expansion rate in the thickness direction of the battery becomes larger; however, the sphericity cannot be too low, which will lead to an increase in the active sites on the surface of the silicon-carbon material, aggravating its side reactions with the electrolyte, which is not conducive to the improvement of cycle stability. The smaller the average particle size of the primary spherical particles, the larger its specific surface area, the greater the side reaction with the electrolyte during the battery charging and discharging process, and the greater the expansion; however, the particle size of the primary spherical particles cannot be too large. A larger particle size of the primary spherical particles is not conducive to improving the compaction density of the negative electrode, and will affect the overall energy density of the battery. Therefore, within a certain range, when the OI value is smaller, the sphericity of the silicon-carbon material can be reduced accordingly, and the particle size can also be reduced accordingly; and when the OI value is larger, the sphericity of the silicon-carbon material needs to be increased accordingly, and the particle size also needs to be increased accordingly. By regulating the relationship between the three, when a specific relationship is met, the battery can further improve its energy density and cycle stability.

[0047] In the present invention, the OI value V of the negative electrode active coating is OI It can be 10-30, for example 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.

[0048] In one example, V OI It is 12-17.

[0049] In the present invention, the OI value V of the negative electrode active coating is OI It can be obtained by testing by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the negative electrode sheet, using an X-ray powder diffraction instrument (such as Shimadzu XRD-6100) to test the negative electrode active coating to obtain a diffraction spectrum, and the intensity of the (004) peak at 2θ of 54°-55° is recorded as I 004 The intensity of the (110) peak with 2θ of 77°-78° is recorded as I 110 , V OI That is I 004 / I 110 .

[0050] In the present invention, the sphericity s of the primary spherical particles may be 0.7-1, for example, 0.7, 0.8, 0.9 or 1.

[0051] In the present invention, the sphericity s of the primary spherical particles can be tested by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, the negative electrode sheet is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasonication, and dried, and the obtained powder is observed with SEM (using high voltage mode). Through image processing software (such as Image Pro Plus), the silicon-carbon material particles in the SEM mirror image at a certain magnification (such as 2500 times) are image analyzed, and at least 10 silicon-carbon material primary spherical particles in the mirror image are selected to obtain the perimeter and area of ​​each particle, and the perimeter equivalent radius and area equivalent radius are calculated respectively, then the sphericity = area equivalent radius / perimeter equivalent radius, and the average value is taken.

[0052] In the present invention, the surface of the negative electrode active coating located on at least one side of the negative electrode current collector may have a first concave portion. The first concave portion is arranged on the surface of the negative electrode active coating, and the first concave portion can provide a certain release space for the volume expansion of the negative electrode active material, and can reduce the extension of the negative electrode current collector caused by the volume expansion of the negative electrode active material, which is conducive to further improving the cycle stability of the battery.

[0053] In the present invention, the first concave portion may include a concave hole or a groove. The first concave portion may be obtained by laser drilling or wire punching technology. When the first concave portion is a groove, the groove may be arranged continuously or in sections. Figure 2 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 2 (a) The grooves are arranged continuously; Figure 2 (b) The grooves are arranged in sections. As can be seen from the figure, the surface of the negative electrode sheet (i.e., the surface of the negative electrode active coating) has several grooves. Figure 2 In (a), the grooves are arranged continuously in the width direction of the negative electrode sheet. Figure 2 In (b), the grooves are arranged in sections in the width direction of the negative electrode sheet. Figure 2 Only the case where the groove is arranged along the width direction of the negative electrode sheet is given, and the groove can also be arranged along the length direction of the negative electrode sheet.

[0054] In the present invention, the depth of the first concave portion may be 5 μm-40 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The depth of the first concave portion has the conventional meaning in the art, and refers to the vertical distance from the lowest point in the first concave portion to the surface of the negative electrode sheet. The depth of the first concave portion can be obtained by testing by conventional methods in the art, for example, using a 3D profiler to test the depths of all first concave portions or at least 20 first concave portions on the surface of the negative electrode active coating, and taking an average value.

[0055] In one example, the depth of the first concave portion is 15 μm-31 μm.

[0056] In the present invention, the width of the first concave portion may be 40 μm-200 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm or 200 μm.

[0057] In one example, the width of the first concave portion is 60 μm-100 μm.

[0058] When the first recess is a recessed hole, the width of the first recessed portion refers to the aperture of the recessed hole. The aperture of the recessed hole has the conventional meaning in this field. When the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a "regular circle", the aperture of the recessed hole is the diameter of the regular circle; when the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a non-"regular circle" (such as an ellipse or an irregular curved polygon), the aperture of the recessed hole is the diameter of an equivalent circle with an area equal to that of the non-"regular circle". The aperture of the recessed hole can be obtained by conventional means in this field, such as by testing the aperture of at least 20 recessed holes on the surface of the negative electrode active coating by a 3D profilometer and taking the average value.

[0059] When the first concave portion is a groove, the width of the first concave portion refers to the width of the groove. The width of the groove has a conventional meaning in the art. The positive projection of the groove on the surface of the negative electrode sheet includes two long sides, and the width of the groove refers to the average distance from one long side to another long side in the length direction or width direction of the negative electrode sheet. Figure 3 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 3 (a)- Figure 3 The two long sides of the groove in (c) are straight lines. Figure 3 The two long sides of the groove in (d) are curved. Figure 3 (a) and Figure 3In (b), the two long sides are arranged in parallel, so that in the width direction of the negative electrode sheet, the vertical distance from any point on one long side to the other long side is equal. In this case, the width of the groove is the vertical distance L1 from any point on one long side to the other long side in the length direction or width direction of the negative electrode sheet. Figure 3 In (c), the two long sides of the groove are straight lines, but they are not set in parallel. Therefore, in the width direction, the size from any point on one long side to the other long side is not equal. In this case, the width of the groove can be averaged, that is, on one long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. Figure 3 In (d), the two long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the width of the groove can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 3 In (d), the two long sides are curved and do not exist. Figure 3 (c) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. The width of the groove can be obtained by conventional means in the art, such as by using a 3D profiler to test the width of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.

[0060] In the present invention, the spacing of the first recesses can be 0.5mm-5mm, for example, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 2mm, 3mm, 4mm or 5mm.

[0061] In one example, the interval between the first recesses is 0.8 mm-1.5 mm.

[0062] When the first concave portion is a concave hole, the spacing of the first concave portion refers to the spacing of the concave holes. The spacing of the concave holes has a conventional meaning in the art. It refers to the shortest distance between the edges of two adjacent concave holes on the surface of the negative electrode sheet. The spacing of the concave holes can be obtained by conventional means in the art, such as by selecting all or at least 10 groups of adjacent concave holes through a 3D profilometer, measuring the spacing, and taking the average value.

[0063] When the first concave portion is a groove, the spacing of the first concave portion refers to the spacing of the grooves. It is understood that when there is only one groove on the surface of the negative electrode sheet, there is no spacing of the grooves. The spacing of the grooves has the conventional meaning in the art, which refers to the average distance between the two adjacent long sides of two adjacent grooves in the length direction or width direction of the negative electrode sheet. Figure 4 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 4 (a) is the case where two adjacent long sides are straight and parallel. Figure 4 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 4 (c) is the case where two adjacent long sides are curved. Figure 4 In (a), the two adjacent long sides are straight and parallel, so in the width direction, the distance from any point on one long side to the other long side is equal. In this case, the spacing of the grooves is the distance L2 from any point on one long side to the other long side in the width direction. Figure 4 In (b), the two adjacent long sides are straight lines, but they are not set in parallel. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can be averaged, that is, on a long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. Figure 4 In (c), the two adjacent long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 4 (c) The two long sides are curved, so there is no Figure 4 (b) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. The spacing of the grooves can be obtained by conventional means in the art, such as by using a 3D profilometer to test the spacing of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.

[0064] In the present invention, the compaction density of the negative electrode sheet can be 1.2 g / cm 3 -1.9g / cm 3 , for example 1.2 g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3, 1.8g / cm 3 or 1.9 g / cm 3 The compaction density here refers to the compaction density actually measured after the battery is disassembled and the negative electrode sheet is taken out during the battery preparation process. It is different from the compaction density obtained by rolling the negative electrode sheet during the battery preparation process. This is because after the negative electrode sheet is assembled into a battery, there will be physical and chemical rebound, resulting in compaction rebound, making the compaction density of the negative electrode sheet actually measured after the battery preparation is completed smaller than the compaction density obtained after rolling.

[0065] In the present invention, the compaction density of the negative electrode sheet can be tested by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the residue on the surface of the negative electrode sheet is washed with deionized water, and then dried. At least 20 sites are selected on the negative electrode sheet, and the thickness of the negative electrode sheet at each site is measured using a micrometer, and the average value h (in μm) is taken; the negative electrode sheet is punched into a disc with a diameter of 44.3 mm using a punching mold, 10 discs are taken, and the mass of each disc is weighed, and the average value m (in mg) is taken, and the surface density M1 = (m-m1) × 100 / 1540.25 is calculated, wherein m1 is the mass of the negative electrode collector in the disc, in mg, and the unit of the surface density is mg / cm 2 The compaction density is calculated using the surface density M1 and the thickness average h, and the formula is as follows: compaction density = M1 × 20 / (h-thickness of the negative electrode current collector), where the unit of the thickness of the negative electrode current collector is μm.

[0066] In the present invention, the lithium-ion secondary battery may further include a positive electrode sheet.

[0067] <Positive electrode>

[0068] In the present invention, the positive electrode sheet may include a positive electrode current collector and a positive electrode active coating located on at least one side of the positive electrode current collector. The positive electrode active coating may include a lithium supplement agent, and the lithium supplement agent may include a chemical formula of Li 5+x Fe y M 1 z The substance and / or chemical formula of O4 is Li 2±a Ni b M c O2; wherein, -0.5≤x≤5 (for example, -0.5, 0, 1, 2, 3, 4 or 5), 0.8≤y≤1.2 (for example, 0.8, 0.9, 1, 1.1 or 1.2), 0≤z≤1 (for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), M 1Including at least one of Mo, Nb, Ti, Zr, Ni, Y, Mn, Cu, Mg and Zn; 0≤a≤0.5 (for example, 0, 0.1, 0.2, 0.3, 0.4 or 0.5), 0≤b≤1 (for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), 0≤c≤1 (for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), M 2 Includes at least one of Mo, Nb, Ti, Zr, Fe, Y, Mn, Cu, Mg and Zn.

[0069] In one example, the lithium supplement includes Li2NiO2 and / or Li5FeO4.

[0070] In the present invention, the mass content c1 of the lithium supplement in the positive electrode active coating may be 0.3%-1%, for example, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.

[0071] In one example, c1 is 0.5%-0.8%.

[0072] The primary spherical particles in the silicon-carbon material have a small average particle size, resulting in a large contact area with the electrolyte. During the battery charge and discharge cycle, the volume expansion will cause the SEI (Solid Electrolyte Interface) film on the surface of the silicon-carbon material to break. The process of SEI film breaking and then reorganizing requires the consumption of active lithium. Although the silicon-carbon material used in the negative electrode sheet of the present invention is a combination of primary spherical particles and secondary spherical particles, it can effectively reduce the consumption of active lithium. However, due to the properties of the silicon material itself, the consumption of active lithium is difficult to completely avoid. Therefore, in order to further improve the cycle life of the battery, a lithium supplement can be added to the positive electrode sheet to increase the content of active lithium in the battery and improve the cycle life of the battery.

[0073] In the present invention, the mass content c1 of the lithium replenisher in the positive electrode active coating can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and then soaked in a DMC solvent for 12 hours, and then rinsed with a DMC solvent to remove the lithium salt attached to the positive electrode sheet, calcined in a muffle furnace at 400° C. for 3 hours, the positive electrode active coating is gently scraped off the surface of the positive electrode current collector, and the mass content of the characteristic elements (such as element Ni and / or element Fe) in the lithium replenisher is measured by an inductively coupled plasma-optical emission spectrometer (ICP-OES), and then the mass content of the lithium replenisher is calculated. The specific operation method is implemented in accordance with GB / T 30902-2014.

[0074] In the present invention, the positive electrode active coating layer may further include a positive electrode active material. The positive electrode active material includes lithium cobalt oxide.

[0075] Related technologies usually repair the SEI film by adding FEC to the electrolyte, thereby inhibiting the occurrence of side reactions and reducing the breakage of silicon-based materials (i.e., silicon-carbon materials in the present invention) during the battery charging and discharging process. In addition, the amount of FEC added needs to increase with the increase of the amount of silicon doping. However, FEC is unstable under high temperature conditions and will decompose to produce a large amount of gas. Too much FEC may cause the battery to produce gas and explode, increasing safety hazards. Therefore, the positive electrode sheet in the present invention adds a lithium supplement, and by reserving excess active lithium, the additional consumption of lithium ions during the SEI film breakage and recombination process is reduced, so that the amount of FEC added to the electrolyte can be reduced while ensuring a high silicon content. Therefore, within a certain range, when the content of FEC increases, the content of the lithium supplement in the positive electrode sheet can be appropriately reduced. If the content of the lithium supplement is too high at this time, it will not only affect the capacity of the positive electrode sheet, but also may cause the side reaction of FEC and the lithium supplement to intensify, increasing safety risks; or, when the content of FEC is reduced, it is necessary to increase the content of the lithium supplement in the positive electrode sheet to improve the electrochemical performance of the lithium-ion battery. When the two meet a specific relationship, the battery can further improve its cycle life and reduce its cycle expansion rate while ensuring safe use.

[0076] In the present invention, the mass content c2 (in %) of FEC in the electrolyte and the mass content c1 (in %) of the lithium supplement in the positive electrode active coating satisfy: c1×c2≤30, for example, 30, 25, 20, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2 or 1.

[0077] In one example, 7≤c1×c2≤24.

[0078] When c1×c2 is low (for example, less than 7), the reserved active lithium provided by the lithium supplement is insufficient to effectively supplement the additional consumption of lithium ions during the breakup and recombination of the SEI film, which is not conducive to improving the electrochemical performance of the battery; and when c1×c2 is high (for example, greater than 24), there is too much FEC and / or too much lithium supplement, and the risk of side reactions of the two increases, which is not conducive to safety performance.

[0079] In one example, 12≤c1×c2≤15.

[0080] It should be noted that, in the calculation of "c1×c2", only the numerical part is used, and the unit is not involved in the calculation. For example, in Example 1, c1 is 0.6%, c2 is 23%, then c1×c2=0.6×23=13.8.

[0081] In the present invention, the length of the positive active coating on the first surface of the positive current collector is greater than the length of the positive active coating on the second surface of the positive current collector. It can be understood that when the positive electrode sheet is coated, there are single-sided coating areas and double-sided coating areas. The single-sided coating area is the positive current collector located in the area, and only one side of the surface has the positive active coating; while the double-sided coating area is the positive current collector located in the area, and both sides of the surface have the positive active coating. This leads to the situation that the lengths of the positive active coatings on the two sides of the positive electrode sheet are not equal. In the present invention, the side with a relatively longer positive active coating on the surface of the positive current collector is defined as the first surface, and the side with a relatively shorter positive active coating is defined as the second surface. The area where the projections of the positive active coating on the first surface and the positive active coating on the second surface overlap in the thickness direction of the positive electrode sheet is the double-sided coating area, and the area where the above projections do not overlap is the single-sided coating area. Due to the special structure of the wound battery, the first surface usually faces the winding center of the winding core, and the second surface is away from the winding center of the winding core.

[0082] In the present invention, the surface of the positive electrode active coating located on the first surface has a second concave portion, and the surface of the positive electrode active coating located on the second surface has a convex portion. By embossing the surface of the positive electrode sheet, a structure having a concave portion on one side and a convex portion on the other side can be obtained. The inventor of the present invention conducted a force analysis on the positive electrode active coating facing the winding center and away from the winding center in the winding core, and found that when a second concave portion is provided on the first surface facing the winding center and a convex portion is provided on the second surface away from the winding center, it is not only beneficial to the structural stability of the positive electrode sheet itself; it can also provide a better buffer space for the volume expansion of the negative electrode sheet, and can improve the cycle life of the battery. Figure 5 The figure shows a schematic diagram of the structure of the winding core in an example of the present invention. It can be seen from the figure that the surface of the positive electrode active coating located on the first surface has a second concave portion, and the surface of the positive electrode active coating located on the second surface has a convex portion. The first surface faces the winding center of the winding core, and the second surface faces away from the winding center of the winding core.

[0083] In the present invention, the shapes of the orthographic projections of the second concave portion and the convex portion on the surface of the positive electrode sheet are not limited, and may be circular, elliptical, linear (including straight lines or wavy lines), polygonal, and the like.

[0084] In the present invention, the positive electrode sheet includes a positive electrode tab welding area, a paste coating area and a blank foil area. The blank foil area refers to the area on the positive electrode current collector that is not coated with the positive electrode active coating except the positive electrode tab welding area. The paste coating area includes a double-sided coating area and a single-sided coating area. Figure 6 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 6 (a) is a top view, Figure 6 (b) is a cross-sectional view along the thickness direction. As can be seen from the figure, the positive electrode sheet includes a positive electrode tab welding area 3, a pasting area 4, and a blank foil area 5, wherein the pasting area 4 includes a double-sided coating area 10 and a single-sided coating area 20.

[0085] In one example, the second recess and the convex portion are located in the pasting area.

[0086] In one example, the second recess and the convex portion are located in the double-sided coating area.

[0087] In one example, the second recess and the convex portion are located in the pasting area and in the double-sided coating area.

[0088] In the present invention, the distance from the second recess to the edge of the positive electrode tab welding area is w1, 0 mm < w1 ≤ 10 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm.

[0089] In the present invention, the distance from the second recess to the edge of the first side of the pasting area is w2, 2 mm ≤ w2 ≤ 40 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 25 mm, 30 mm, 35 mm, or 40 mm. The first side is the side where the positive electrode tab welding area is provided.

[0090] In the present invention, the distance from the second recess to the edge of the second side of the pasting area is w3, 2 mm ≤ w3 ≤ 25 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or 25 mm. The second side is the side opposite to the side where the positive electrode tab welding area is provided.

[0091] In the present invention, the distance from the second recess to the edge of the third side of the pasting area is w4, 0 mm < w4 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, or 20 mm. The third side is the side of the pasting area close to the first winding end.

[0092] In the present invention, the distance from the second recess to the boundary line between the double-sided coating area and the single-sided coating area is w5, where 0 mm < w5 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, or 20 mm.

[0093] By controlling w1, w2, w3, w4, and w5, it is possible to ensure that the positive electrode sheet does not shed powder, which is beneficial to improving the cycle life of the battery.

[0094] As Figure 7 Shown is a top view schematic diagram of the first surface of the positive electrode sheet in an example of the present invention. As can be seen from the figure, the first surface has a plurality of second recesses 6. The distance from the second recess 5 to the edge of the positive electrode tab welding area 3 is w1. The distance from the second recess 6 to the edge of the first side of the paste coating area 4 is w2. The distance from the second recess 6 to the edge of the second side of the paste coating area 4 is w3. The distance from the second recess 6 to the edge of the third side of the paste coating area 4 is w4. The distance from the second recess 6 to the boundary line between the double-sided coating area 10 and the single-sided coating area 20 is w5.

[0095] In the present invention, the depth of the second recess can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, or 40 μm. The height of the convex portion can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, or 40 μm.

[0096] In one example, the depth of the second recess is 10 μm - 30 μm. The height of the convex portion is 10 μm - 30 μm.

[0097] In the present invention, the depth of the second recess and the height of the convex portion have their conventional meanings in the art. The depth of the second recess refers to the vertical distance from the lowest point in the second recess to the surface of the positive electrode sheet. The height of the convex portion refers to the vertical distance from the highest point on the convex portion to the surface of the positive electrode sheet. The depth of the second recess and the height of the convex portion can be obtained by testing with conventional methods in the art. For example, using a 3D profiler, at least 20 second recesses or 20 convex portions are selected on the surface of the positive electrode sheet, the depth of each second recess is measured, and the average value is taken to obtain the depth of the second recess; the height of each convex portion is measured, and the average value is taken to obtain the height of the convex portion.

[0098] In the present invention, the width of the second concave portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The width of the convex portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0099] In one example, the width of the second concave portion is 1 mm to 3 mm, and the width of the convex portion is 1 mm to 3 mm.

[0100] In the present invention, when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the second concave portion is the diameter of the regular circle; when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the second concave portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. Similarly, when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the convex portion is the diameter of the regular circle; when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the convex portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. The width of the second concave portion and the width of the convex portion can be obtained by conventional methods in the art, for example, by using a 3D profiler, selecting at least 10 second concave portions and 10 convex portions on the surface of the positive electrode sheet, measuring the width of each second concave portion and the width of the convex portion, and taking the average values ​​respectively.

[0101] In the present invention, the spacing of the second concave portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The spacing of the convex portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0102] In one example, the spacing between the second concave portions is 1 mm to 3 mm, and the spacing between the convex portions is 1 mm to 3 mm.

[0103] In the present invention, the spacing of the second concave portions refers to the shortest distance between the edges of the orthographic projections of two adjacent second concave portions on the surface of the positive electrode sheet, and similarly, the spacing of the convex portions refers to the shortest distance between the edges of the orthographic projections of two adjacent convex portions on the surface of the positive electrode sheet. The spacing of the second concave portions and the spacing of the convex portions can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, selecting at least 10 groups of adjacent second concave portions or convex portions on the surface of the positive electrode sheet, measuring the spacing, and taking the average value.

[0104] In the present invention, the composition of the positive electrode active coating layer can be selected conventionally in the art.

[0105] <Electrolyte>

[0106] In the present invention, the electrolyte may further include at least one of a lithium salt, an additive and an organic solvent. The lithium salt may include, for example, lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethylsulfonyl imide), lithium difluorobis(oxalatophosphate), lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl lithium and lithium tetrafluoroborate. The additives include, for example, vinyl carbonate, vinyl carbonate, vinyl sulfate, fluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, acetonitrile, propionitrile, butyronitrile, succinonitrile, malononitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sunflower dinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3,6-hexane trinitrile, 1,3,5-pentane tricarbonitrile, 1,2,3-propane tricarbonitrile, 1,2,6-hexane trinitrile, acrylonitrile, crotonitrile, trans-butene dinitrile, glycerol trinitrile and trans-hexene dinitrile. The organic solvent includes, for example, carbonate solvents and / or carboxylic acid ester solvents. The carbonate solvent includes, for example, ethylene carbonate (EC) and / or at least one of the following solvents substituted or unsubstituted with fluorine: propylene carbonate (PC), dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate. The carboxylate solvent includes, for example, at least one of the following fluorine-substituted or unsubstituted solvents: ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate (PP), ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate and ethyl n-butyrate.

[0107] In the present invention, the lithium ion secondary battery may further include a separator, and the separator may be a conventional one in the art.

[0108] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0109] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0110] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0111] The following examples are used to illustrate the lithium ion secondary battery of the present invention.

[0112] Example 1

[0113] Prepare the battery as follows:

[0114] (1) Preparation of positive electrode sheet

[0115] Lithium cobalt oxide, lithium supplement (Li2NiO2), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 96.4:0.6:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and a positive electrode slurry is prepared; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a 100 μm thick aluminum foil. Positive electrode sheet; a positive electrode tab welding area of ​​a fixed size is provided on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 20 mm), and the nickel tab is welded in the above-mentioned positive electrode tab welding area by laser; and then, after being passed through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0116] The width of the second recess is 2 mm, the depth is 20 μm, and the spacing is 2 mm; w1 is 7 mm, w2 is 27 mm, w3 is 15 mm, w4 is 7 mm, and w5 is 7 mm.

[0117] (2) Preparation of negative electrode sheet

[0118] Graphite material (artificial graphite, average particle size d2 of secondary particles is 12.3 μm), silicon-carbon material (the number of primary spherical particles accounts for 0.54 of the total number of primary spherical particles and secondary spherical particles, the average particle size d1 of primary spherical particles is 4.2 μm, the sphericity s of primary spherical particles is 0.95, and the mass content of element Si in the silicon-carbon material is 70%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 88.6:8.4:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is manufactured on the surface of the negative electrode sheet using a laser;

[0119] Among them, the mass content of element Si in the negative electrode active coating is 5.9%, d2 / d1 is 2.93, V OI 15.4, VOI / s is 16.21, V OI / d1 is 3.67; the width of the groove is 80.2 μm, the depth is 20.3 μm, and the spacing is 1.3 mm.

[0120] (3) Preparation of electrolyte

[0121] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; FEC and lithium salt LiPF6 are dissolved in the organic solvent to obtain an electrolyte; wherein the mass content c2 of FEC in the electrolyte is 23%, and the mass content of LiPF6 in the electrolyte is 12.5%;

[0122] Among them, c1×c2 is 13.8.

[0123] (4) Preparation of batteries

[0124] The positive electrode sheet prepared in step (1), the separator (comprising a polyethylene base film with a thickness of 4 μm, a ceramic layer with a thickness of 2 μm on one side of the base film, a polymethyl methacrylate adhesive layer with a thickness of 0.5 μm on the other side of the base film, and a polyvinylidene fluoride + polymethyl methacrylate adhesive layer with a thickness of 2.5 μm on the outer surface of the ceramic layer) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core; and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.

[0125] Example 2

[0126] Prepare the battery as follows:

[0127] (1) Preparation of positive electrode

[0128] Lithium cobalt oxide, lithium supplement (Li2NiO2), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 96.5:0.5:1:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to prepare a positive electrode slurry; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 15 mm), and a nickel tab is laser welded in the positive electrode tab welding area; after being rolled, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion and a convex portion; the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0129] The width of the second recess is 1 mm, the depth is 10 μm, and the spacing is 1 mm; w1 is 5 mm, w2 is 20 mm, w3 is 10 mm, w4 is 5 mm, and w5 is 5 mm.

[0130] (2) Preparation of negative electrode sheet

[0131] Graphite material (artificial graphite, average particle size d2 of secondary particles is 10.2 μm), silicon-carbon material (the number of primary spherical particles accounts for 0.33 of the total number of primary spherical particles and secondary spherical particles, the average particle size d1 of primary spherical particles is 4.8 μm, the sphericity s of primary spherical particles is 0.85, and the mass content of element Si in the silicon-carbon material is 70%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 88.6:8.4:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0132] Among them, the mass content of element Si in the negative electrode active coating is 5.9%, d2 / d1 is 2.13, V OI is 16.9, V OI / s is 19.88, V OI / d1 is 3.52; the width of the groove is 60.6 μm, the depth is 15.5 μm, and the spacing is 0.8 mm.

[0133] (3) Preparation of electrolyte

[0134] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; FEC and lithium salt LiPF6 are dissolved in the organic solvent to obtain an electrolyte; wherein the mass content c2 of FEC in the electrolyte is 30%, and the mass content of LiPF6 in the electrolyte is 12.5%;

[0135] Among them, c1×c2 is 15.

[0136] (4) Preparation of batteries

[0137] The positive electrode sheet prepared in step (1), the separator (including a polyethylene base film, a ceramic layer with a thickness of 2 μm on one side of the base film, a polymethyl methacrylate adhesive layer on the other side of the base film, and a polyvinylidene fluoride + polymethyl methacrylate adhesive layer on the outer surface of the ceramic layer) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core; and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.

[0138] Example 3

[0139] Prepare the battery as follows:

[0140] (1) Preparation of positive electrode

[0141] Lithium cobalt oxide, lithium supplement (Li2NiO2), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 96.2:0.8:1:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to prepare a positive electrode slurry; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 25 mm), and a nickel tab is laser welded in the positive electrode tab welding area; after being rolled, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion and a convex portion; the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0142] The width of the second recess is 3 mm, the depth is 30 μm, and the spacing is 3 mm; w1 is 9 mm, w2 is 34 mm, w3 is 20 mm, w4 is 10 mm, and w5 is 10 mm.

[0143] (2) Preparation of negative electrode sheet

[0144] Graphite material (artificial graphite, average particle size d2 of secondary particles is 14.9 μm), silicon-carbon material (the number of primary spherical particles accounts for 0.75 of the total number of primary spherical particles and secondary spherical particles, the average particle size d1 of the primary spherical particles is 3.1 μm, the sphericity s of the primary spherical particles is 0.8, and the mass content of element Si in the silicon-carbon material is 70%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 88.6:8.4:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0145] Among them, the mass content of element Si in the negative electrode active coating is 5.9%, d2 / d1 is 4.81, V OI 12.3, V OI / s is 15.38, V OI / d1 is 3.97; the width of the groove is 99.7 μm, the depth is 30.5 μm, and the spacing is 1.5 mm.

[0146] (3) Preparation of electrolyte

[0147] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; FEC and lithium salt LiPF6 are dissolved in the organic solvent to obtain an electrolyte; wherein the mass content c2 of FEC in the electrolyte is 15%, and the mass content of LiPF6 in the electrolyte is 12.5%;

[0148] Among them, c1×c2 is 12.

[0149] (4) Preparation of batteries

[0150] The positive electrode sheet prepared in step (1), the separator (including a polyethylene base film, a ceramic layer with a thickness of 2 μm on one side of the base film, a polymethyl methacrylate adhesive layer on the other side of the base film, and a polyvinylidene fluoride + polymethyl methacrylate adhesive layer on the outer surface of the ceramic layer) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core; and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.

[0151] Example 4 Group

[0152] This group of examples is used to verify the impact of changes in the "average particle size d2 of secondary particles".

[0153] This group of examples is carried out with reference to Example 1, except that the average particle size d2 of the secondary particles is changed, as follows:

[0154] Example 4a, d2 is 8.2 μm; wherein d2 / d1 is 1.95, V OI is 29.3, V OI / s is 30.84, V OI / d1 is 6.98;

[0155] Example 4b, d2 is 19.7 μm; wherein d2 / d1 is 4.69, V OI 10.5, V OI / s is 11.05, V OI / d1 is 2.5.

[0156] Example 5 Group

[0157] This group of examples is used to verify the influence of the change of the "average particle size d1 of the primary spherical particles".

[0158] This group of examples is carried out with reference to Example 1, except that the average particle size d1 of the primary spherical particles is changed, as follows:

[0159] Example 5a, d1 is 1.1 μm; wherein d2 / d1 is 11.18, V OI / d1 is 14;

[0160] Example 5b, d1 is 5.9 μm; wherein d2 / d1 is 2.08, V OI / d1 is 2.61.

[0161] Example 6 Group

[0162] This group of examples is used to verify the impact of changes in "the value of the number of primary spherical particles to the total number of primary spherical particles and secondary spherical particles".

[0163] This group of examples is carried out with reference to Example 1, except that the number ratio of spherical particles is changed once, as follows:

[0164] Example 6a, the number of primary spherical particles accounts for 0.14 of the total number of primary spherical particles and secondary spherical particles;

[0165] Example 6b, the number of primary spherical particles accounts for 0.88 of the total number of primary spherical particles and secondary spherical particles;

[0166] In Example 6c, all silicon-carbon materials are primary spherical particles, that is, the number of primary spherical particles accounts for 1 of the total number of primary spherical particles and secondary spherical particles;

[0167] In Example 6d, the number of primary spherical particles accounts for 0.05 of the total number of primary spherical particles and secondary spherical particles.

[0168] Example 7 Group

[0169] This group of examples is used to verify the influence of the change of "the mass content of element Si in the negative electrode active coating".

[0170] This group of examples is carried out with reference to Example 1, except that the mass content of element Si in the negative electrode active coating is regulated by changing the mass content of graphite material and silicon-carbon material in the negative electrode slurry, as follows:

[0171] In Example 7a, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 92.1:4.9:0.4:0.1:2.5, wherein the mass content of element Si in the negative electrode active coating is 3.4%;

[0172] In Example 7b, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 80:17:0.4:0.1:2.5, wherein the mass content of element Si in the negative electrode active coating is 11.9%;

[0173] In Example 7c, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 94.2:2.8:0.4:0.1:2.5, wherein the mass content of element Si in the negative electrode active coating is 2%;

[0174] In Example 7d, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 76:21:0.4:0.1:2.5, wherein the mass content of element Si in the negative electrode active coating is 14.7%.

[0175] Example 8

[0176] This example is used to verify the influence of the change of "sphericity s of primary spherical particles".

[0177] The method is carried out in accordance with Example 1, except that s is 0.7; wherein V OI / s is 22.

[0178] Example 9 Group

[0179] This group of examples is used to verify the OI / s and V OI / d1” changes.

[0180] This group of examples is carried out with reference to Example 2 and Example 3, except that the sphericity s and the average particle size d1 of the primary spherical particles are changed to adjust V OI / s and V OI / d1, as follows:

[0181] Example 9a is carried out in accordance with Example 2, except that d1 is 3.1 μm, s is 0.8, d2 / d1 is 3.29, V OI / s is 21.13, V OI / d1 is 5.45;

[0182] Example 9b is carried out in accordance with Example 3, except that d1 is 4.8 μm, s is 0.95, d2 / d1 is 3.10, V OI / s is 12.95, V OI / d1 is 2.56.

[0183] Example 10

[0184] This embodiment is used to verify the influence of changing the “type of the first recess”.

[0185] The method is carried out in accordance with Example 1, except that a laser is used to make recessed holes on the surface of the negative electrode sheet, wherein the width of the recessed holes is 80.5 μm, the depth is 25.2 μm, and the spacing is 500 μm.

[0186] Example 11 Group

[0187] This group of examples is used to verify the impact of changes in "lithium supplements".

[0188] This group of examples is carried out with reference to Example 1, except that no lithium supplement is added to the positive electrode sheet or different types of lithium supplement are replaced, as follows:

[0189] In Example 11a, the lithium supplementing agent is removed from the positive electrode slurry; that is, the mass ratio of lithium cobalt oxide, positive electrode conductive agent and positive electrode binder is 97:1:2;

[0190] In Example 11b, the lithium supplement is replaced with the same mass of Li5FeO4.

[0191] Example 12 Group

[0192] This group of examples is used to verify the influence of the change of "the mass content c1 of the lithium supplement agent in the positive electrode active coating".

[0193] This group of examples is carried out with reference to Example 1, except that c1 is changed, as follows:

[0194] In Example 12a, c1 is 0.3%; wherein the mass ratio of lithium cobalt oxide, lithium supplement, positive electrode conductive agent and positive electrode binder is 96.7:0.3:1:2, and c1×c2 is 6.9;

[0195] In Example 12b, c1 is 1%; wherein the mass ratio of lithium cobalt oxide, lithium supplement, positive electrode conductive agent and positive electrode binder is 96:1:1:2, and c1×c2 is 23.

[0196] Embodiment 13

[0197] This example is used to verify the influence of “whether the second concave portion is located on the surface of the positive electrode active coating on the first surface and whether the convex portion is located on the surface of the positive electrode active coating on the second surface”.

[0198] The method is carried out in accordance with Example 1, except that the embossing treatment is performed from the second surface to the first surface, that is, the surface of the positive electrode active coating on the second surface has a second concave portion, and the surface of the positive electrode active coating on the first surface has a convex portion.

[0199] Embodiment 14

[0200] This embodiment is used to verify the influence of "whether the single-sided coating area has a second concave portion".

[0201] The process is carried out in accordance with Example 1, except that embossing is performed on the single-sided coating area and the double-sided coating area (avoiding the positive electrode tab welding area).

[0202] Example 15 Group

[0203] This group of embodiments is used to verify the impact of changes in "w1, w2, w3, w4 and w5".

[0204] This group of examples is carried out with reference to Example 1, except that w1, w2, w3, w4 and w5 are changed as follows:

[0205] In embodiment 15a, w1 is 0.5 mm, w2 is 2 mm, w3 is 2 mm, w4 is 0.5 mm, and w5 is 0.5 mm;

[0206] In Example 15b, w1 is 10 mm, w2 is 40 mm, w3 is 25 mm, w4 is 20 mm, and w5 is 20 mm.

[0207] Example 16 Group

[0208] This group of embodiments is used to verify the impact of the change of "c1×c2".

[0209] This group of examples is carried out with reference to Example 2 and Example 3, except that c1×c2 is regulated by changing the mass content c2 of fluoroethylene carbonate in the electrolyte, as follows:

[0210] Example 16a, carried out with reference to Example 2, except that c2 is 15%, c1×c2 is 7.5;

[0211] Example 16b is carried out with reference to Example 3, except that c2 is 30% and c1×c2 is 24.

[0212] Embodiment 17

[0213] This embodiment is used to verify the influence of “no first recess is provided on the surface of the negative electrode active coating”.

[0214] The same procedure is carried out as in Example 1, except that no groove is made on the surface of the negative electrode sheet.

[0215] In the above embodiments, the convex portions all meet the following requirements: a height of 3 μm-40 μm, a width of 0.2 mm-8 mm, and a spacing of 0.5 mm-8 mm.

[0216] Embodiment 18

[0217] This example is used to verify the influence of “no second concave portion and convex portion being provided on the surface of the positive electrode active coating layer”.

[0218] The same process is carried out as in Example 1, except that no embossing treatment is performed.

[0219] Comparative Example 1

[0220] The process is carried out in accordance with Example 1, except that the artificial graphite is primary particles with an average particle size of 6.1 μm.

[0221] Comparative Example 2

[0222] The process is carried out in accordance with Example 1, except that the average particle size d2 of the artificial graphite secondary particles is 22.6 μm.

[0223] Comparative Example 3

[0224] The method is carried out with reference to Example 1, except that the mass ratio of the graphite material, the silicon-carbon material, the negative electrode conductive agent, the negative electrode dispersant and the negative electrode binder is 65.5:31.5:0.4:0.1:2.5, wherein the mass content of element Si in the negative electrode active coating is 22%.

[0225] Comparative Example 4

[0226] This group of comparative examples is used to verify the influence of the change of the "average particle size d1 of the primary spherical particles".

[0227] This comparative example is carried out with reference to Example 1, except that the average particle size d1 of the spherical particles is changed, as follows:

[0228] Comparative Example 4a, d1 is 0.8 μm;

[0229] In Comparative Example 4b, d1 is 6.5 μm.

[0230] Comparative Example 5

[0231] This group of comparative examples is used to verify the impact of changes in "the mass content c2 of fluoroethylene carbonate in the electrolyte".

[0232] This comparative example was carried out with reference to Example 1, except that c2 was changed, as follows:

[0233] In comparative example 5a, c2 is 0, i.e., no fluoroethylene carbonate is added to the electrolyte;

[0234] Comparative Example 5b, c2 is 40%.

[0235] Test Case

[0236] (1) 45℃ high temperature cycle test

[0237] The batteries prepared in the examples and comparative examples were subjected to a 45°C high temperature cycle test. The specific test method is as follows:

[0238] Place it in a constant temperature room at 45℃ for 2h, charge it to 4.2V with 3C constant current, then charge it to 4.48V with 2C constant current and constant voltage, cut off at 0.05C, and place it for 10min; then discharge it to 3.0V with 0.7C, and repeat this cycle for 500 times. When the battery is fully charged at the 500th cycle, its thickness is h1 and its discharge capacity is C1. When the battery is fully charged for the first time, its thickness is h0 and its discharge capacity is C0. Then C1 / C0 is the capacity retention rate after 500 cycles, and (h1-h0) / h0 is the thickness expansion rate after 500 cycles. The results are recorded in Table 1.

[0239] (2) Volume energy density test

[0240] The batteries prepared in the examples and comparative examples were tested for volume energy density, and the specific test method is as follows:

[0241] The battery was charged to the upper voltage limit (4.48V) at a current of 0.2C, then charged at a constant voltage until the current dropped to 0.02C, and then discharged at a current of 0.2C to 3.0V, with the discharged energy recorded as E; the thickness, width and length of the battery were measured and the product of the three was calculated to obtain the volume of the battery recorded as V. The calculation formula for volume energy density is VED = E / V, and the results are recorded in Table 1.

[0242] Table 1

[0243]

[0244]

[0245]

[0246] As can be seen from Table 1, the battery of the present invention can achieve both high energy density and excellent cycle stability compared with the comparative example. Compared with Example 1, since the graphite material of Comparative Example 1 uses primary particles, the energy density of the battery is lower and the thickness expansion rate is higher. The content of fluoroethylene carbonate in Comparative Example 5b is relatively high, so the high temperature performance of the battery is poor.

[0247] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: Including negative electrode sheet and electrolyte; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector, wherein the negative electrode active coating comprises a negative electrode active material; the negative electrode active material comprises a graphite material and a silicon-carbon material; the graphite material comprises secondary particles, and the silicon-carbon material comprises primary spherical particles and secondary spherical particles formed by a plurality of the primary spherical particles; The electrolyte comprises fluoroethylene carbonate, and the mass content of fluoroethylene carbonate in the electrolyte is c2≤30, in units of %; The mass content of element Si in the negative electrode active coating is 1.5%-15%; The average particle size d2 of the secondary particles is 6 μm-20 μm; The average particle size d1 of the primary spherical particles is 1 μm to 6 μm.

2. The lithium ion secondary battery according to claim 1, wherein In the negative electrode active coating, the amount of the primary spherical particles accounts for 0.1-0.9 of the total amount of the primary spherical particles and the secondary spherical particles; preferably 0.3-0.8; And / or, the mass content of element Si in the negative electrode active coating is 3.5%-12%; And / or, the silicon-carbon material includes a material formed by filling silicon and / or oxidized silicon in pores of porous carbon; And / or, the mass content of element Si in the silicon-carbon material is 30%-80%.

3. The lithium ion secondary battery according to claim 1 or 2, wherein: 1.33≤d2 / d1≤20; preferably, 2≤d2 / d1≤5; and / or, d2 is 10 μm-15 μm; And / or, d1 is 3 μm-5 μm.

4. The lithium ion secondary battery according to claim 1 or 2, wherein: The OI value V of the negative electrode active coating OI , the sphericity s of the primary spherical particles and the average particle size d1 of the primary spherical particles, in μm, satisfy: 10≤V OI / s≤35, and 2≤V OI / d1≤15; Preferably, 12 ≤ V OI / s≤22, and 2.5≤V OI / d1≤5.5; More preferably, 15 ≤ V OI / s≤20, and 3.5≤V OI / d1≤4.

5. The lithium ion secondary battery according to claim 4, wherein: The OI value V of the negative electrode active coating OI 10-30; preferably 12-17; And / or, the sphericity s of the primary spherical particles is 0.7-1.

6. The lithium ion secondary battery according to claim 1 or 2, wherein: The surface of the negative electrode active coating layer located on at least one side of the negative electrode current collector has a first concave portion; Preferably, the depth of the first concave portion is 5 μm-40 μm; Preferably, the width of the first concave portion is 40 μm-200 μm; Preferably, the spacing between the first recesses is 0.5 mm-5 mm.

7. The lithium ion secondary battery according to claim 1 or 2, wherein: The lithium-ion secondary battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating located on at least one side surface of the positive electrode current collector; The positive electrode active coating includes a lithium supplement agent, and the lithium supplement agent includes a chemical formula of Li 5+x Fe y M 1 z The substance and / or chemical formula of O4 is Li 2±a Ni b M 2 c O2 substances, where -0.5≤x≤5, 0.8≤y≤1.2, 0≤z≤1, M 1 Including at least one of Mo, Nb, Ti, Zr, Ni, Y, Mn, Cu, Mg and Zn; 0≤a≤0.5, 0≤b≤1, 0≤c≤1; M 2 including at least one of Mo, Nb, Ti, Zr, Fe, Y, Mn, Cu, Mg and Zn; Preferably, the mass content c1 of the lithium supplement in the positive electrode active coating is 0.3-1, in %; Preferably, the lithium supplement comprises Li2NiO2 and / or Li5FeO4.

8. The lithium ion secondary battery according to claim 7, wherein: The mass content c2 of fluoroethylene carbonate in the electrolyte, in units of %, and the mass content c1 of the lithium supplement in the positive electrode active coating, in units of %, satisfy: c1×c2≤30; Preferably, 7≤c1×c2≤24; More preferably, 12≤c1×c2≤15.

9. The lithium ion secondary battery according to claim 1 or 2, wherein: The lithium-ion secondary battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating located on at least one side surface of the positive electrode current collector; The length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector; The region where the projection in the thickness direction of the positive electrode active coating on the first surface overlaps with the projection of the positive electrode active coating on the second surface is the double-sided coating region, and the region where the projections do not overlap is the single-sided coating region; The surface of the positive electrode active coating on the first surface has a second recess, and the surface of the positive electrode active coating on the second surface has a protrusion; Preferably, the positive electrode sheet includes a positive electrode tab welding region, a pasting region, and a blank foil region, and the second recess and the protrusion are located in the pasting region; Preferably, the positive electrode sheet includes a pasting region, the pasting region includes the double-sided coating region and the single-sided coating region, and the second recess and the protrusion are located in the double-sided coating region; Preferably, the depth of the second recess is 3 μm - 40 μm, the width of the second recess is 0.2 mm - 8 mm, and the spacing of the second recess is 0.5 mm - 8 mm; Preferably, the height of the protrusion is 3 μm - 40 μm, the width of the protrusion is 0.2 mm - 8 mm, and the spacing of the protrusion is 0.5 mm - 8 mm.

10. The lithium ion secondary battery according to claim 9, wherein The positive electrode sheet includes a positive electrode tab welding region, a pasting region, and a blank foil region, and the pasting region includes the double-sided coating region and the single-sided coating region; The distance from the second recess to the edge of the positive electrode tab welding region is w1, 0 mm < w1 ≤ 10 mm; And / or, the distance from the second recess to the edge of the first side of the pasting region is w2, 2 mm ≤ w2 ≤ 40 mm, and the first side is the side where the positive electrode tab welding region is provided; And / or, the distance from the second recess to the edge of the second side of the pasting region is w3, 2 mm ≤ w3 ≤ 25 mm, and the second side is the side opposite to the side where the positive electrode tab welding region is provided; And / or, the distance from the second recess to the edge of the third side of the pasting region is w4, 0 mm < w4 ≤ 20 mm, and the third side is the side of the pasting region close to the first winding end; And / or, the distance from the second recess to the boundary line between the double-sided coating region and the single-sided coating region is w5, 0 mm < w5 ≤ 20 mm.

Citation Information

Patent Citations

  • Fast-charging high-energy-density lithium ion battery and application thereof

    CN117410545A

  • Electrochemical device and electronic device

    CN118198275A

  • Preparation method of high-energy-density lithium iron phosphate battery

    CN118589057A

  • Lithium ion secondary battery

    EP4456170A2

  • Negative electrode active material, material of mixed negative electrode active material, negative electrode for non-aqueous electrolyte secondary battery, lithium ion secondary battery, method for producing negative electrode active material, and method for producing lithium ion secondary battery

    US20190006661A1

Cited By

  • Negative electrode sheet and lithium-ion secondary battery

    WO2026145181A1